APLIKASI PENGENALAN OBJEK WISATA KOTA BATAM MENGGUNAKAN MARKER AUGMENTED REALITY - Siregar, Ade Fadhilah; Hutabri, Ellbert (LPPM Universitas Putera Batam, 2023)
Batam City is an island in the north of Indonesia because it is at the crossroads between countries such as Singapore, Malaysia, Vietnam, Cambodia, and Thailand, so Batam City is a business and tourist destination. To increase domestic and international tourist visits, the Batam City Government has carried out promotions in various ways such as promotions through the Batam City Culture and Tourism Office website, social media. But there is no application to promote tourist attractions in Batam City, it is necessary to build an application for recognizing tourist objects in Batam City which includes visualization of tourist objects in 3D and information about tourist objects to make it easier for tourists to choose tourist objects according to their wishes. This research developed an application to recognize tourism objects in Batam City using augmented reality markers with the application of the SDLC (System Development Life Cycle) Waterfall model method. The augmented reality (AR) technology tracking method used in this study is marker-based tracking. Based on the results of functional testing, shows that the application functions properly. The results of the user satisfaction test gave a good value so the results found that the application was very well received by users.